IMPLEMENTASI PROGRAM PEMBELAJARAN TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN TAHFIDZUL QUR’AN SYECH AHMAD CHATIB AL-MINANGKABAWI - Saipul Anwar; Iswantir M (CV. Aksara Global, 2023)
Tahfidzul Qur'an Syech Ahmad Chatib al-Minangkabawi Islamic Boarding School, found proud academic achievements, especially in the MTQ, MHQ branches at the District, Regency, Provincial and National levels. This research is qualitative field research. Data was obtained through observation, interviews and documentation studies. Informants were selected using the